A Living Wage for The Bahamas: Estimates, Potentials, and Problems - Archer, Lesvie; Hogg, Bridget Sophia; Perumal, Vijaya; Saunders, Olivia; Johnson, Brittney (International Journal of Bahamian Studies, 2021)
This report describes how living wage estimates were calculated for New Providence and Grand Bahama. This report uses primary and secondary sources and is inspired by the Anker methodology. We calculated that 2625 and 3550 were needed each month as the gross living wage for a full-time worker who must sustain a family of four in New Providence and Grand Bahama, respectively. We estimated the net living wage to be 2500 per month for New Providence and 3400 for Grand Bahama. Our estimates are almost 200% higher than the minimum wage and nearly 130% higher than the poverty line for New Providence; for Grand Bahama, they are almost 300% higher than the minimum wage and 160% higher than the poverty line. The study should inform national discussions on public policy matters related to reducing the country’s cost of living, improving its income equity, and pursuing economic justice for all.